Ternary deep eutectic solvent magnetic molecularly imprinted polymers for the dispersive magnetic solid‐phase microextraction of green tea. Issue 17 (16th July 2018) - Li, Guizhen; Row, Kyung Ho
Abstract: Ternary deep eutectic solvent magnetic molecularly imprinted polymers grafted on silica were developed for the selective recognition and separation of theophylline, theobromine, (+)‐catechin hydrate, and caffeic acid from green tea through dispersive magnetic solid‐phase microextraction. A new ternary deep eutectic solvent was adopted as a functional monomer. The materials obtained were characterized by FTIR spectroscopy, field emission scanning electron microscopy, transmission electron microscopy, NMR spectroscopy, and powder X‐ray diffraction. The practical recovery of the theophylline, theobromine, (+)‐catechin hydrate, and caffeic acid isolated with ternary deep eutectic solvent magnetic molecularly imprinted polymers in green tea were 91.82, 92.13, 89.96, and 90.73%, respectively, and the actual amounts extracted were 5.82, 4.32, 18.36, and 3.69 mg/g, respectively. The new method involving the novel material coupled with dispersive magnetic solid‐phase microextraction showed outstanding recognition, selectivity and excellent magnetism, providing a new perspective for the separation of bioactive compounds.